Research on the Impact of Digital Investment on Green Performance of Listed Enterprises - Xia, Yuhan (Transactions on Social Science, Education and Humanities Research, 2024)
Based on the data of Chinese listed enterprises from 2017 to 2022, this paper examines the impact of digital investment on the green performance of listed enterprises. The study found that digital investment is negatively correlated with the green performance of listed enterprises, which is still valid after the robustness test. According to the heterogeneity analysis, digital investment has a more significant negative effect on the green performance of state-owned enterprises. The research conclusions not only reveal environmental effects of digital investment, but also broaden the research perspective of digital investment and corporate green performance, which has vital enlightening significance for the government to promote the construction of the ecological civilization and enterprises to improve green performance.